Evaluation of HbA1c Level and Other Risk Factors in Diabetic Retinopathy: A Study of Type 2 Diabetic Patients Attending in a Tertiary Level Hospital - Hoque, Sayama; Muttalib, MA; Islam, Md Imtiajul; Khanam, Parvin Akter; Choudhury, Subhagata (KYAMC Journal, 2017)
Background: Retinopathy is the leading cause of blindness in persons with diabetes. Strict monitoring and maintenance of normal blood glucose specially HbA1c and prevention of different risk factors can prevent and delay the diabetic retinopathy. The purpose of the study was to explore the factors influencing or related to the development of the diabetic retinopathy with spcial concern to the HbA1c levels. Materials and Methods: We studied 400 type 2 diabetic patients in this cross-sectional study which was conducted in the out-patient department of BIRDEM hospital, Bangladesh. The randomly selected patients were evaluated for the presence of retinopathy through the review of their registered diabetic guide book. We included sociodemographic information, blood pressure, anthropometry (height, weight, BMI) and lipid profile of the patients. Glycaemic status was assessed by HbA1c (HbA1c was categorized into 3 groups) and plasma glucose levels. We used Student's t-test, Chi-square test and logistic regression analysis to determine and quantify the association of diabetic retinopathy with various risk factors specially HbA1c. Results: 400 type 2 diabetic patients (male 166 and female 234) were studied. The prevalence of retinopathy was 12.3%; male 12.7%, female 12.0%. Increasing HbA1c categories above 7.0% were significantly associated with increased prevalence of retinopathy (4.2 vs 12.3 vs 18.1%;c2 = 12.529, p < .01). Logistic regression models of univariate analysis showed that the risk of retinopathy at HbA1c categories >7.0% was (OR = 3.22; 95% CI: 1.12-9.25) and the risk was strongly increased at the HbA1c categories 8% (OR = 5.07; 95% CI: 1.90-13.50). Advanced age (OR = 2.92; 95% CI: 1.44-5.91), longer duration of diabetes (OR = 3.08; 95% CI: 1.49-6.37), presence of hypertension (OR = 2.42; 95% CI: 1.14-5.16), FBG (OR = 1.139; 95% CI: 1.036-1.251), blood glucose 2 hours ABF (OR = 1.124; 95% CI: 1.046-1.207) and SBP (OR = 1.033; 95% CI: 1.011-1.056) had significant association with retinopathy. Conclusions: HbA1c categories >7.0% is an important risk factor for the development of retinopathy. Poor glycaemic control, advanced age, longer duration of diabetes, hypertension are other significant risk factors of diabetic retinopathy. KYAMC Journal Vol. 6, No.-2, Jan 2016, Page 614-619